Geological and structural analysis of the Hwange area-Northwest Zimbabwe: using remotely sensed data and geographic information systems (GIS) - Chivasa, Mufaro (Not Specified, 2023)
There is a continuous need to locate more targets for coal exploration and evaluation of geological structures in the north-west coalfields in Zimbabwe. Conventional methods of analysing geological structures and field mapping are being hindered by inaccessibility of some areas and thick covers of Recent sediments. Remote sensing has been found to be a valuable method of identifying lithologic units and geological structures in the· area. Integration of the remotely sensed data in a 2D GIS resulted in recognition of spatial relationships between lithologic units, geological structures , coal seams and vegetation patterns. The Hwange area constitutes the western part of the Mid-Zambezi Karoo basin. The area consist of a wide spectrum of rocks ranging from Precambrian gneisses, Proterozoic schists and granulites, Karoo sediments to Tertiary and Recent sands. The area has been affected by a number of faults and shears some of which post date the Karoo sediments. These faults are an expression of the major tectonic events associated with this area. Some of the faults have been attributed to the effects of the Zambezi Rift System. Fault zones in the area, such as the Deka, Entuba and Inyantue Zones have been recognised as part of this system and these divide the Lower Karoo rocks into different coalfields. To try and evaluate the outcrop patterns and geological structures in the Hwange area, all the available geological and structural data were captured in a spatial database. The diversity of data incorporated in the spatial database demanded the need for a structured database design approach. The Entity-Relationship model was used to conceptualise the geological data of the ' Hwange area This model was transformed into the Relational Model that formed the implementation model of the database. Landsat 5 TM data covering the area from the Zimbabwean winter (20 June 1984) path 172, row 73 were also analysed for the information required to locate Karoo rift faults and the distribution of lithologic units associated with coal. The use of directional filters in the E-W and NE-SW directions and vegetation reflection characteristics during the dry season (June 1984) proved very effective in mapping fractures in the Karoo rocks. Landsat TM image enhancement techniques such as principal components analysis, edge enhancement, decorrelation stretching, band ratios; and colour composites made following these techniques, allowed mapping of different lithological units and discrimination between Karoo rocks and the crystalline basement rocks. Lineament analysis defined E-W, ENE-WSW, NE-SW and NW-SE conjugate sets of lineaments. The first three sets are related to the regional fracture zones of the Zambezi rift system The Entuba fault zone was found to be associated with most of the fractures affecting the Hwange coalfields. These have a dominant NE-SW and ENE-WSW trend in the Western Areas, Wankie Concession, Chaba, Entuba and Sinamatella coalfields. The E-W trending fracture set is dominated by joint sets in the Karoo basalt covering the north-west portion of the Hwange Coalfields. These show no relationship with the linear features of the Zambezi Rift system The NW-SE trending lineaments are dominantly developed on tilted bedding planes in the Karoo rocks as well as a few sparse joints in the Karoo basalt. Overlaying enhanced Landsat TM images on mapped faults and lithology data in a GIS revealed a number of features along the Entuba zone which were not previously known. The south-western part of the Entuba inlier was shown to consist of a synformal fold plunging to the south and bound on both sides by strike slip faults. Several kinematic indicators such as displacement of sedimentary strata have shown that the Entuba fault displays right lateral strike-slip coupled with dipslip movement. Proximity analysis using borehole data (depth to top and bottom of a coal seam) showed that most of the lineaments in the area are normal faults which have caused considerable displacements of the main coal seam Comparison of seam depth across most of these faults within coalfields and from one field to another shows that local and regional variations in depths of the main seam is primarily a function of vertical displacements along the faults over and above variations in the morphology of the pre-Karoo floor. The Entuba field was found to have greatest vertical variations over very short distances across faults, with depths varying from 60m to 520m from west to east over distances of less than 500m This part of the field has been partly affected by extensive normal faults, some of which can be traced for more than 10km. In the Hwange area, the Karoo rocks have been down faulted into a rift margin which is in turn divided into smaller fault blocks by intra-rift faulting. The shape of the fault blocks are further controlled by the orientation of the post-Karoo faults which have also down faulted the main coal seam Exploration activity in the area should also seek to establish the locations of these faults to help further decipher variations in depths of coal seams.